PALB2 as a potential prognostic biomarker for colorectal cancer. (August 2020) - Pan, Weiyu; Lu, Kui; Wang, Weixia; Yao, Junxia; Hou, Yingyong
Graphical abstract: Highlights: We evaluated the prognostic value of PALB2 gene in colorectal cancer. PALB2 gene could be novel prognostic biomarkers for colorectal cancer. Function analyses showed that PALB2 is primarily involved in the DNA repair process. Abstract: Partner and localizer of BRCA2 (PALB2) is regarded as a colorectal cancer (CRC) risk gene, but the prognostic implication of PALB2 in CRC remains unclear. In this study, we evaluate the prognostic value of the gene copy number alteration (CNA) and mRNA expression of PALB2 in The Cancer Genome Atlas (TCGA) database, and then validated with our database. We downloaded the copy number and mRNA data of PALB2 from TCGA database and examined the relationship among the genetic alterations, expression levels and survival outcomes. Gene ontology (GO) analysis was performed to study the function of PALB2. cBioPortal database was used to explore the potential co-expression genes of PALB2. There were 6.3% (37 of 582) CRC patients diagnosed as PALB2 gene deletion. The PALB2 deletion group expressed significantly lower of PALB2 mRNA than the non-deletion group ( P < 0.001). Survival analysis showed that PALB2 deletion was significantly associated with shorter disease-free survival (DFS) ( P = 0.026) and overall survival (OS) ( P = 0.028). Low mRNA expression of PALB2 correlated with shorter OS ( P < 0.001). Multivariate analysis also confirmed that PALB2 deletion and low mRNA expression of PALB2 were independent prognostic factors of poor OS in CRC ( P = 0.019, 0.034, respectively). In validation cohort, negative expression of PALB2 was associated with shorter OS ( P = 0.006) in stage I patients. Multivariate analysis confirmed that negative expression of PALB2 was a poor-prognostic factor ( P = 0.002). GO analysis and co-expression analysis investigated that PALB2 is primarily involved in the DNA repair process. These results suggest that PALB2 gene copy number deletion and low mRNA expression could be novel prognostic biomarkers for CRC.